Temporal focus, dual-system self-control, and college students’ short-video addiction: a variable-centered and person-centered approach - Liu, Yang; Huang, Yaqing; Wen, Lan; Chen, Peng; Zhang, Shuyue (Frontiers in Psychology, 2025)
BackgroundShort video addiction has become increasingly prevalent among college students. It can negatively impact their physical and mental health, yet its influencing factors and underlying mechanisms require further exploration. Time focus and self-control are recognized as critical determinants in shaping addictive behaviors.ObjectiveGrounded in the I-PACE theory, this study examines the relationship between emotional and cognitive responses (various temporal focuses and dual systems of self-control) and short video addiction, while also investigating the mediating roles of inhibitory and initiation control.MethodsMethodologically, it integrates both variable-centered and person-centered approaches, utilizing the Time Focus Scale, Multidimensional Self-Control Scale, and Short Video Addiction Scale. A total of 2,239 university students participated in the survey.ResultsThe results revealed the following: (1) Past and present time focus were positively correlated with short video addiction, while future time focus showed a negative correlation. Inhibitory self-control was positively associated with short video addiction, whereas initiatory self-control was negatively correlated. Variable-centered analysis demonstrated that past and present time focus positively predicted short video addiction, with inhibitory self-control mediating the relationship between these time orientations and addiction. Conversely, initiatory self-control played a mediating role between future time focus and addiction risk, with a negative predictive effect on the likelihood of short video addiction. (2) Person-centered analysis identified four categories of short video addiction: non-addicted (12.68%), low-risk addiction (34.21%), moderate-risk addiction (42.20%), and high-risk addiction (10.89%). (3) Logistic regression analysis indicated that students with excessive past and present time focus were more likely to fall into the high-risk addiction category, while those employing inhibitory self-control strategies were more likely to be categorized into low, moderate, or high-risk addiction groups. Students utilizing initiatory self-control were less likely to develop high-risk addiction. Female students were more likely than male students to fall into the low, moderate, or high addiction categories, and only children were more likely to belong to the moderate or high-risk addiction categories than non-only children.ConclusionThis study emphasizes the pivotal role of time focus and dual-system self-control in the intervention and prevention of short video addiction,further highlighting the role of emotional and cognitive responses in the development of short-video addiction. The implications of the findings, as well as the limitations of the study, are also discussed.